GENOTOXIC EFFECTS OF BORIC ACID AND BORAX IN ZEBRAFISH, DANIO RERIO USING ALKALINE COMET ASSAY - (:unkn) unknown (EXCLI JOURNAL MANAGING OFFICE, 2015)
The present study is conducted to determine the potential mechanisms of Boron compounds, boric acid (BA) and borax (BX), on genotoxicity of zebrafish Danio rerio for 24, 48, 72 and 96-hours acute exposure (level: 1, 4, 16, 64 mg/l BA and BX) in semi-static bioassay experiment. For that purpose, peripheral erythrocytes were drawn from caudal vein and Comet assay was applied to assess genotoxicity. Acute (96 hours) exposure and high concentrations of boric acid and borax increases % tail DNA and Olive tail moment. Genotoxicity was found for BA as concentration-dependent and BX as concentration and time dependent manner. In general, significant effects (P < 0,05) on both concentrations and exposure times were observed in experimental groups. DNA damage was highest at 96 h and 24 h for all BX and BA concentrations, respectively in peripheral blood of D. rerio. For the first time, our study demonstrates the effect of waterborne BA and BX exposure on genotoxicity at the molecular level, which may contribute to understanding the mechanism of boric acid and borax-induced genotoxicity in fish.
Keywords: boric acid; borax; genotoxicity; Comet assay; Danio rerio; INDUCED DNA-DAMAGE; MICRONUCLEUS TEST; BORON-COMPOUNDS; ACUTE TOXICITY; IN-SITU; FISH; TROUT; CELLS; ERYTHROCYTES; MOLYBDENUM